Tramadol use is associated with reduced 28-day mortality in ICU patients after cardiac surgery: a retrospective study based on the MIMIC-IV database - Xu, Jingyan; Zhang, Yang; Gao, Rongqing (Frontiers in Pharmacology, 2026)
BackgroundTo evaluate the association between tramadol use and short-term outcomes, including 28-day mortality, intensive care unit (ICU) mortality, and ICU length of stay, in critically ill patients undergoing cardiac surgery.MethodsThis retrospective cohort study included 3,544 participants from the MIMIC-IV database. A comprehensive analytical approach was employed, including multivariate Cox regression, subgroup analysis, propensity score matching (PSM), inverse probability weighting (IPW), doubly robust estimation, and E-value calculation. Receiver operating characteristic (ROC) curves and the DeLong test were used to compare the predictive performance of different opioids, and SHAP analysis was employed for model interpretation.ResultsTramadol use was consistently associated with a significant reduction in 28-day mortality across all models. The hazard ratios (HR) ranged from 0.305 to 0.341 after rigorous adjustment and matching (all P < 0.05). Subgroup analyses demonstrated the robustness of this protective association, and a significant interaction was observed with respect to surgery type after PSM. Furthermore, tramadol demonstrated superior predictive performance for 28-day mortality (AUC = 0.603) compared to other opioids, including fentanyl, hydromorphone, morphine, and oxycodone AUC range: 0.523–0.597). However, no significant association was found with secondary outcomes like ICU mortality or length of stay.ConclusionTramadol administration is independently associated with a significantly lower risk of 28-day mortality in cardiac surgery patients, showing better predictive utility than other common opioids, which may inform postoperative analgesic strategies.